2020
DOI: 10.3847/1538-4357/ab7897
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA Spectroscopic Survey in the HUDF: The Cosmic Dust and Gas Mass Densities in Galaxies up to z ∼ 3

Abstract: Using the deepest 1.2 mm continuum map to date in the Hubble Ultra Deep Field, which was obtained as part of the ALMA Spectroscopic Survey (ASPECS) large program, we measure the cosmic density of dust and implied gas (H 2 +H I) mass in galaxies as a function of look-back time. We do so by stacking the contribution from all H-band selected galaxies above a given stellar mass in distinct redshift bins, r > M M z , dust

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
86
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 97 publications
23
86
0
1
Order By: Relevance
“…z∼3, showing minor changes of this parameter between z=3 and 1 and a steep decline from z=1 to 0, thus following very closely the evolution of the cosmic SFR density in this redshift range (Decarli et al 2016a(Decarli et al , 2020Riechers et al 2019;Magnelli et al 2020). It is thus interesting to ask, what is the nature of the galaxies that dominate r H2 with redshift?…”
Section: Molecular Gas Budgetmentioning
confidence: 79%
“…z∼3, showing minor changes of this parameter between z=3 and 1 and a steep decline from z=1 to 0, thus following very closely the evolution of the cosmic SFR density in this redshift range (Decarli et al 2016a(Decarli et al , 2020Riechers et al 2019;Magnelli et al 2020). It is thus interesting to ask, what is the nature of the galaxies that dominate r H2 with redshift?…”
Section: Molecular Gas Budgetmentioning
confidence: 79%
“…In this appendix, we compare the fiducial stellar masses we derive for sources in our study using FAST ( > z 2.5) with those derived from the MAGPHYS software (da Cunha et al 2008) which is used in many of the other ASPECS analyses (e.g., Magnelli et al 2020). The stellar masses we estimated are in agreement with our fiducial results, with the median and mean stellar mass derived by MAGPHYS being 0.07 dex and 0.36 dex higher, respectively, with a median absolute difference between the two mass estimates of 0.38 dex.…”
Section: Appendix a Comparison Of Our Fiducial Stellar Mass Estimatesmentioning
confidence: 99%
“…The dust content, relative to the stellar and gas mass, associated with these galaxies should be lower than the one associated with more massive galaxies. The companion paper, Magnelli et al (2020), used stacking to explore the dust content galaxies with different stellar mass ranges. They found that the comoving dust mass density associated with galaxies with   M M 10 10 * at 1<z<3 is fairly low, and that most of the dust mass is associated with more massive galaxies.…”
Section: Causes For the Flattening Of The Number Countsmentioning
confidence: 99%